Introduction to Judaism - Cherry, Shai.; Teaching Company (Chantilly, Va. : Teaching Co., 2004)
Shai Cherry, professor of Jewish thought at Vanderbilt University, presents the unfolding of the religious aspects of the Jewish civilization from the Hebrew Bible to today, while keeping an eye on the historical background against which those changes within Judaims have occured.
lect. 1. Torah, Old Testament, and Hebrew Bible -- lect. 2. From Israelite to Jew -- lect. 3. Repentance -- lect. 4. Study -- lect. 5. Prayer -- lect. 6. Deeds of loving kindness -- lect. 7. Messianism -- lect. 8. The coming world -- lect. 9. Sabbath -- lect. 10. Law and spirit -- lect. 11. Fall holidays -- lect. 12. Spring holidays -- lect. 13. Minor holidays, then and now -- lect. 14. Medieval Jewish philosophy, Maimonides -- lect. 15. Medieval Jewish mysticism, Kabbalah -- lect. 16. Evil and suffering, bibical and Rabbinic -- lect. 17. Evil and suffering, medieval and modern -- lect. 18. Emancipation, enlightenment, and reform -- lect. 19. Orthodox Judaisms -- lect. 20. Israel and Zionism -- lect. 21. American Judaisms -- lect. 22. Women and Jewish law -- lect. 23. Judaism and the other --lect. 24. The chosen people?
DVD, region 1.
Course nos. 4621 and 6422 on booklets; Course no. 6423 on discs.
Instructed by Shai Cherry.
Keywords: Judaism; Judaism -- History